Evaluation Of The Engine Lecturers’ Performance in Improving Academic Quality at PIP Makassar - Tandibura, Frans; Ma’na, Pertus; Rantererung, Corvis L; Limbong, Sunarlia (Mudir : Jurnal Manajemen Pendidikan, 2024)
This research aimed to evaluate the management of lecturer performance, the lecturers' performance improves the academic quality, and the academic quality results from the performance of lecturers at Politeknik Ilmu Pelayaran (PIP) Makassar. This research used a qualitative approach with a case study research type and descriptive using primary and secondary data from ten informants in the engineering study program. The research results show that lecturer performance assessment management has three main tasks, namely education, research and community service. The development of a university is largely determined by the quality of the human resources. Lecturer performance plays a very important role in improving the academic quality of higher education as the main pillar in the education and teaching process, as well as playing a role in research and scientific development. Stages of lecturer performance (ability to design learning/RPS, mastery of courses, methods). Stages of education quality (process, infrastructure, learning media, activities in learning). Research publications and PKM were routine in conducting research and publications, where research publications contribute the development of science and support the growth of knowledge in the field of study. It can be concluded that a lecturer is required to perform optimally so as to create professional and high-quality productivity results on the lecturer's performance as seen from the output, namely quality graduates, the success of alumni reflects the quality of education received by the lecturer. As a recommendation for lecturers to improve the academic reputation quality of the institution and help strengthen scientific contributions in publications.